Qualitative Interviewing with Adults: Diverse Approaches and Applications - Wąsiński, Arkadiusz (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The objective of this chapter is to provide a concise, synthetic overview of thelinguistic and methodological intricacies involved in comprehending the research interviewin the social sciences. It also puts forward a system for organising these concepts basedon key criteria in the research process. An in-depth interpretive analysis has resulted in fourframeworks for classifying research interview typologies, based on differentiating criteriasuch as: the degree of structure, the respondent’s freedom of expression, thematic focus,the quality of the relationship between participants, and the stage of theory development.Moreover, the chapter identifies various types of qualitative interviews and highlights theirspecific characteristics as applied to exploring the subjective worlds of narrators’ experiences.The text emphasises the significance of a researcher’s methodological awareness forthe effective selection and use of interviews. Indeed, the authors contend that given themultiplicity and diversity of methodological perspectives, the rationality of the qualitativeapproach is ultimately reflected in the rationality of the discourse led by the researcher.